EFEKTIVITAS BAHAN PENGAWET ALAMI DARI TANAMAN TEMBELEKAN (Lantana camara L) PADA BEBERAPA JENIS KAYU TERHADAP SERANGAN RAYAP TANAH (Coptotermes sp.) - Safitri, Risky; Erniwati, Erniwati; Hapid, Abdul (Universitas Tadulako, 2014)
Many favorable properties of wood are available in almost all parts of the world, easily obtained in different shapes and sizes, relatively easy to process, as well as very decorative appearance. However, wood also has a weakness that could be damaged by a variety of factors either biological, physical, mechanical or chemical. In reality, the main factors causing damage to the wood are fungi, bacteria, insects and marine animals (marine borer). The organisms might damage the wood because they make as a shelter or as feed. Therefore, there should be conducted wood preservation to overcome the unfavorable properties of the woods. Wood preservation aims to extend the use of low-class durability of timber species such as Bayur (Pterospermum sp), Durian (Durio zibethinus) and Benuang (Octomeles sumatrana Miq). This study aimed at determining the effectiveness of a natural preservative tembelekan (Lantana camara L). The research was conducted at the Forestry Sciences Laboratory, Department of Forestry, Forestry Faculty, Tadulako University and Talise Mantikulore Sub-district, started from May to July 2013. The study was designed with the method of completely randomized design (CRD) with three wood species treatment, namely bayur, durian and benuang. Each was preserved with a natural preservatives of tembelekan extract with a concentraation of 13,04%. There were 10 samples of each type of wood, consisting of 5 test samples preserved and 5 controls (without preserrvatives). There were 30 test samples. The parameters observed were preservative effectiveness of the sample weight after feeding on soil termites. The study shows that highest natural preservative effectiveness on benuang wood was preserved with the sample weight loss of 2,25% and the lowest on bayur wood was preserved with the sample weight loss of 3,47% when they were compared with the control sample (without preservative). Using tembelekan extract might increase wood resistance to soil termite attacks. Keywords: Captotermes sp, Durio zibethinus, Lantana camara L, Octomeles sumatrana Miq, tembelekan.